2009
DOI: 10.1002/nau.20733
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and urodynamic results of a 3‐month percutaneous posterior tibial nerve stimulation treatment in patients with multiple sclerosis‐related neurogenic bladder dysfunction

Abstract: These results have demonstrated that PTNS is effective to suppress NDO in MS patients after PTNS. Although long-term efficacy of PTNS is known, the findings showed prominent improvements on the clinical and urodynamic outcome, we think that the use of PTNS for DO in MS patients will be promising in clinical practice in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 32 publications
3
57
0
2
Order By: Relevance
“…The precise mechanism of action is unknown, but it has been proposed that PTNS inhibits bladder activity by depolarizing somatic sacral and lumbar afferent fibres. Initial studies of the use of PTNS using either percutaneous or transcutaneous electrodes in MS neurogenic DO have shown it to be an effective, safe and well-tolerated treatment [5,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanism of action is unknown, but it has been proposed that PTNS inhibits bladder activity by depolarizing somatic sacral and lumbar afferent fibres. Initial studies of the use of PTNS using either percutaneous or transcutaneous electrodes in MS neurogenic DO have shown it to be an effective, safe and well-tolerated treatment [5,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…67 Other clinical studies have also demonstrated that peripheral electrical stimulation of the posterior tibial nerve improves clinical and urodynamic outcome and provides long-term efficacy though suppressing neurogenic detrusor overactivity in MS patients. 68,69 However, MS patients with urinary retention due to detrusor underactivity are not suitable for this treatment. 70 The LION (laparoscopic implantation of neuroprosthesis) procedure on the sacral plexus is worth trying if the classical percutaneous technique has been unsuccessful.…”
Section: Neuromodulation Of the Peripheral Nervous Systemmentioning
confidence: 99%
“…However, the mainstay of available data are from non-neurogenic overactive bladder patients [35,36], but some recent studies also provided data from neurological patients, that is, MS and Parkinson's disease [37][38][39][40][41][42][43][44]. However, randomized controlled trials (RCTs) are lacking for PTNS and TTNS in the neurological population, and there are currently no long-term data or systematic data on HRQoL available.…”
Section: External Neuromodulationmentioning
confidence: 99%